KEEFEKTIFAN PERMAINAN ULAR TANGGA SEBAGAI MEDIA PENILAIAN TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 1 SINJAI - Febrian, Tiara; Djungmingin, Sulastriningsih; Hasriani (STKIP Subang, 2026)
This study aims to (1) analyze the effectiveness of using the snake and ladder game as an assessment tool for understanding biographical texts among 10th grade students at Sinjai 1 Public High School. (2) examine the differences in the results of understanding biographical texts among 10th grade students at Sinjai 1 Public High School before and after the implementation of the snake and ladder game as an assessment tool. The type of research used is quantitative research with a single-group pre-post-test design. Data collection techniques were carried out through written tests divided into pre-tests and post-tests. The population of this study was all tenth-grade students at SMA Negeri 1 Sinjai, while the research sample was 28 students from class X.1, determined using purposive sampling. Data analysis was conducted using descriptive statistical analysis and inferential statistical analysis. The results showed that the students' biography text assessment results were in the very poor category, with an average score of 38.93 in the range of 0-49. After the implementation of the snake and ladder game assessment media, the students' assessment results showed a significant increase with an average score of 84.75 in the range of 70-84. Based on the results of the paired sample t-test using SPSS, a significance value (Sig.2-tailed) < 0.000 was obtained, which is smaller than 0.05 with a t-count of -36.781, so the hypothesis is accepted. Thus, it can be concluded that the Snakes and Ladders game is effective in teaching biographical texts to 10th-grade students at Sinjai State High School 1